The Evaluation of Harm and Purity Transgressions in Africans: A Paradigmatic Replication of Rottman and Young (2019) - Adetula, Adeyemi; Forscher, Patrick; Basnight-Brown, Dana; Wagge, Jordan; Namalima, Takondwa, Rex; Kaphesi, Frank, Ephraim; Kaliyapa, Wickson; Mulungu, Kennedy; Silungwe, Walusungu; Gopye, Polycarp, Chamkat; Malingumu, Winfrida; Azouaghe, Soufian; et al. (My University, 2021)
Improving the generalizability of psychology findings to a culture requires sampling participants in that culture. Yet psychology studies rarely sample from African populations, even though it represents 17% of the overall world population. This study aimed to conduct an African-led replication study to test whether Rottman and Young’s “mere-trace” hypothesis of moral reasoning (that people are more sensitive to the dosage of harm-based transgressions than purity transgressions) extends to several African communities. We used a training method developed by the Collaborative Replication and Education Project (CREP) to support and train 23 African collaborators. During this process, we conducted a paradigmatic replication of Rottman’s and Young’s test of the mere trace hypothesis in Egypt, Malawi, Morocco, Mozambique, Nigeria, South Africa, and Tanzania. [We did not find/We found] evidence for the main interaction effect (bdomain x dose = xxx) of transgression severity on the moral wrongness judgment of impure and harmful violations. [We did/ However, we did not] replicate Rottman and Young's findings among Africans. This project helped improve the research capacity of our participating African sites and will support other researchers in collaborating with African scholars.
Supplemental Materials: https://osf.io/kvhzg/
Keywords: Africa; corelab; morality; Psychological Science; replication